Happinimal Project: Kampanye Kebebasan Hewan agar Sejahtera - Zayyana Khairunnisa Lubis; Banna Rosyid Madani; Rizky Satya Reswara; Tutut Chusniyah (Universitas Negeri Malang, 2023)
The Happinimal Project program is a social-based Animal Freedom campaign that aims to maintain animal welfare. The term